2023
DOI: 10.1021/jacs.3c04213
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex Emission and Förster Resonance Energy Transfer in Polycyclic Aromatic Hydrocarbon-Based Bischromophoric Cyclophanes and Homo[2]catenanes

Amine Garci,
Seifallah Abid,
Arthur H. G. David
et al.

Abstract: Energy transfer and exciplex emission are not only crucial photophysical processes in many living organisms but also important for the development of smart photonic materials. We report, herein, the rationally designed synthesis and characterization of two highly charged bischromophoric homo[2]catenanes and one cyclophane incorporating a combination of polycyclic aromatic hydrocarbons, i.e., anthracene, pyrene, and perylene, which are intrinsically capable of supporting energy transfer and exciplex formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 111 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Thus, the energy transfer from TCNPh to the CT complex should be the reason that the strong CT emission was achievable even with small ratios of TAT-nC (Figure 4f). 84,85 These results indicated that the strategy for regulating the molecular arrangement through alkyl chains has no relation to the mixing ratio of the donor and acceptor.…”
Section: Crystallographic Analysis Showed That the Synergistic Effect...mentioning
confidence: 98%
“…Thus, the energy transfer from TCNPh to the CT complex should be the reason that the strong CT emission was achievable even with small ratios of TAT-nC (Figure 4f). 84,85 These results indicated that the strategy for regulating the molecular arrangement through alkyl chains has no relation to the mixing ratio of the donor and acceptor.…”
Section: Crystallographic Analysis Showed That the Synergistic Effect...mentioning
confidence: 98%
“…Conjugated molecules or ions not only have special physical characteristics such as strong nonlinear photoelectric properties, but they are also important in the study of novel materials, including polymer batteries, electronic conductors, and organic light-emitting devices. Among them, cyclic compounds have excellent optoelectronic properties, and their open-shell singlet ground-state double radicals have strong electron coupling characteristics and broad application prospects in magnetic devices [ 6 , 7 , 8 ]. In the past decade, the use of the para -connected phenyl ring as a scaffold for carbon-based materials sparked a research frenzy in the synthesis of cyclic compounds [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant advancements were made by Adachi and co-workers by designing spatially separated donor–acceptor systems for TADF. , Hitherto, this design principle has mainly been exploited in covalent molecular systems that often suffer from arduous syntheses with meager reaction yields and aggregation-caused quenching. A promising alternative approach is the non-covalent supramolecular strategy, where specifically tailored subunits provided by the host and the guest afford desirable photofunctional properties in their host–guest complexes. A first very successful example for this approach was recently reported by Wong and Chou where the stabilization of triplet excitons and exploration of photofunctional properties from purely organic triplet generators in solution have been accomplished with the help of a guest embedded in a host cage, leading to solid-state materials with excellent OLED performance . However, in this system, the binding strength between host and guest in solution remained low compared to cyclophane-based host–guest systems, , and TADF properties could only be studied in a reliable way in the solid state, like for other donor–acceptor TADF systems relying on the non-covalent approach. Further, activating the triplet harnessing pathways via a non-covalent strategy using organic chromophores remains a formidable challenge because, in addition to a sufficient binding strength, such a heavy atom-free, purely organic solution-state triplet generator demands an efficient triplet state population, a low singlet–triplet energy gap (Δ E S–T ), and its stabilization from vibrational dissipation and oxygen quenching.…”
Section: Introductionmentioning
confidence: 99%